Pengaruh Model Pembelajaran Quantum Teaching Terhadap Hasil Belajar Kognitif Peserta Didik Ditinjau dari Kecerdasan Majemuk - Pramudita, Ratna (Desimal: Jurnal Matematika, 2018)
Seeing the influence of quantum teaching model on learning outcomes of cognitive learners in terms of multiple intelligences is an objective of this study. For the purpose can be achieved then the type of research used is Quasy Experiment. The technique used in sampling used is a random technique class. Data collection techniques used are tests, interviews, observations, and questionnaires. The test hypothesis used is the test of variance analysis of two streets (Anava 2 Road). However, before the hypothesis is tested, preliminary tests have been performed, namely Validity test, difficulty level, differentiation, reliability, normality and homogeneity test. Based on test results that have been analyzed found that there is the influence of cognitive learning outcomes of learners using quantum teaching model. Furthermore, there are differences in cognitive learning outcomes between learners who have logical-mathematical intelligence with learners who have interpersonal and naturalist intelligence. Further, There is no interaction between learning models and intelligence of logical-mathematical, interpersonal, and naturalist learners to cognitive learning outcomes of learners.